Plasmon-coupled Au-nanochain functionalized PEDOT:PSS for efficient mixed tin–lead iodide perovskite solar cells. Issue 9 (6th January 2022) - Song, Jiaxing; Yin, Xinxing; Hu, Lin; Su, Zhen; Jin, Yingzhi; Deng, Dan; Li, Zaifang; Wang, Guannan; Bao, Qinye; Tian, Wenjing
Abstract : Au nanochains with a coupled plasmonic nanostructure were first introduced into PEDOT:PSS used as a HTL to fabricate mixed Sn–Pb PSCs. Abstract : Au nanochains with a coupled plasmonic nanostructure were first introduced into PEDOT:PSS used as a hole transport layer to fabricate mixed tin–lead PSCs. The improved electrical properties and the promotion of optical absorption contributed to a high PCE of 19.2%. Moreover, the PSCs show substantial enhancement in stability.